Soft Tissue Calcifications in the Orofacial Region - Monalisa Muduli (Institute of Medico-legal Publications Pvt Ltd, 2020)
The main purpose of this article is to present a review of soft tissue calcification in Orofacial region. Itcan be systemically evaluated by using a simple algorithm based on the detailed clinical information anddistribution pattern of these calcified lesions. The calcification of soft tissues belongs to a large group oflesions. Radiologists often detect calcifications in their daily work. For dental practitioners, this reviewshould be of interest in encountering the soft tissue calcification in the orofacial region.